DAR DAN Perputaran Persediaan Serta Pengaruhnya Terhadap Profitabilitas Perusahaan Tekstil Dan Garmen Yang Terdaftar Di Indeks Saham Syariah Indonesia - Rizky Aprilian Kusuma Dewi; Ari Prasetyo (Universitas Airlangga, 2016)
The purpose of this reserach is to find out the significant effect of the two variable debt to assets ratio and inventory turn over of the profitability with the measuring instrument Return On Assets. The method used in this study is quantitative method with secondary data sources. The samples in this study are the tekstil and garment companies that are still registered in Indonesia Sharia Stock Index, publishing their three month report completely from 2012 to September 2015. There are seven companies that will become the samples. The technique used in this study is panel data regression analysis technique. The result of this research indicate that the inventory turnover partially provide a significant influence on ROA, and debt to assets ratio partially provide an unsignificant influence on ROA. Simultaneously, inventory turn over dan debt to assets ratio providea significant influence ROA.